ORIGAMI: AN ALTERNATIVE MEDIA TO TEACH PROCEDURE TEXT IN SPEAKING - Mitra, Muhammad Mujtaba (Universitas Islam Lamongan, 2019)
Procedure text is the text that has to be mastered by senior high school. The purpose of the text is to give a clue how to do something through some steps. The students should experience the lesson in order to help them to know that activity is on their daily life and to apply the worldly education